Time reflexivity in social work interaction: A literature review on migration, time and temporality for social work practice - Hjärpe, Teres; Tumminelli, Giuseppina; Ferraro, Giuseppa (Trabajo Social Global, 2025)
Introduction. In this article we explore how findings from existing research on time, temporality and migration can be relevant to social work practice and inform social workers’ interaction with migrating individuals. In social work literature, time mainly appear as part of the procedural knowledge as organizationally decided time frames and deadlines for work which is sometimes internalized and taken for granted and sometimes contested. Challenging this tendency to equalize time with the clock, we explore how time and temporality tied to other forms of knowledge may play a different role in social work and be a constructive tool in interaction with individuals who have migratory experiences.Methods.Findings are presented from a configurative literature review in which in total 41 articles meeting inclusion criteria were analyzed and thematically synthetized into three main themes. Results.Findings in the first theme Time and powerserve to demonstrate how power operates with time as a resource, and how power relations are visible in the different ways social workers and migrants are governed by, experiencing and relating to time. In the second theme Recalibrating, migratory experiences and consequences are put in relation to life plans and prospects in a life course perspective. The literature on the third and most extensive theme Waiting identifies this state as being connected to both slowness, uncertainty and frustration, as wellas work, agency and hope. Theoretically informed by Barbara Adam’s dynamic approach to time—time as social, multifaceted, contextual and positional—we suggest that these findings can be useful for time reflexivityin social workers’ interactions with individuals with migration experiences. Discussion and conclusions.We find time reflexivity to be relevant for social work practice at four levels. Three of these levels have relevance for the direct interaction: the preconditional (reminding social worker ofpower asymmetry), the relational (time as a meaning making tool) and the operative (filling waiting time with meaning). A fourth level is the organizational, and it concerns the social workers’ work environment and working conditions. Beyond social work practice, time reflexivity can inform policy makers in strivings to create a transparent and dignified attendance of migrants within public organizations. We invite academic scholars and social work practitioners to give further empirical content to our proposed practice theory; time reflexivity.
Keywords: Time; Temporality; Migration; Social Work; Reflexivity; Recognition.